2022
DOI: 10.1093/genetics/iyac185
|View full text |Cite
|
Sign up to set email alerts
|

Imaginal disk growth factors are Drosophila chitinase-like proteins with roles in morphogenesis and CO2 response

Abstract: Chitinase-like proteins (CLPs) are members of the family 18 glycosyl hydrolases, which include chitinases and the enzymatically inactive CLPs. A mutation in the enzyme's catalytic site, conserved in vertebrates and invertebrates, allowed CLPs to evolve independently with functions that do not require chitinase activity. CLPs normally function during inflammatory responses, wound healing, and host defense, but when they persist at excessive levels at sites of chronic inflammation and in tissue-remodeling disord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Thus, the dorsal appendages provide a readout for proper tube formation ( Fig 1D” and 1D”‘ ). The defects in Idgf-null dorsal appendages peaked at 8–10 hours after the CO 2 pulse and returned to the basal level by 27 hours [ 3 ]. The wild-type flies developed normally despite the loss of cortical actin apparent at 30 minutes post CO 2 exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the dorsal appendages provide a readout for proper tube formation ( Fig 1D” and 1D”‘ ). The defects in Idgf-null dorsal appendages peaked at 8–10 hours after the CO 2 pulse and returned to the basal level by 27 hours [ 3 ]. The wild-type flies developed normally despite the loss of cortical actin apparent at 30 minutes post CO 2 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We previously tested how different CO 2 exposure regimes affected dorsal appendage development, including a single 1-minute pulse of 100% CO 2 , which increased defects in Idgf-null eggs but not in control eggs; a 1-minute pulse of 100% CO 2 every 12 hours for 3.5 days, which increased defects in Idgf-null eggs but not in control eggs; and continuous 20% CO 2 for up to eight days, which produced no increase in defects in either genotype [ 3 ]. Note that CO 2 makes up about 0.04% of the ambient atmosphere [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the down-regulation of Cht10 results in severe phenotypes, including wing differentiation failure, ecdysis disturbance, growth inhibition, pupariation failure, and death ( Dong et al 2020 , Qu et al 2021 ). Meanwhile, it was reported that IDGFs were essential for Drosophila fertility ( Sustar et al 2023 ). Despite extensive studies on chitinase function in numerous insects, its role in the flesh fly remains unexplored.…”
Section: Introductionmentioning
confidence: 99%